An Empirical Test of the Weak-Form Efficiency: the Case of Thai Equity Mutual Funds - Jenwittayaroje, Nattawut (NIDA Business Journal, 2025)
Most studies on weak-form efficient market hypothesis (Fama, 1970) were done on stock indices or individual stocks. To fill such gap, this study rather tests weak-form market efficiency on Thai equity mutual funds. The results from both runs tests and variance ratio tests on 40 Thai equity mutual funds’ daily returns from March 2019 to December 2024 indicate that we cannot reject the null hypothesis that the daily returns of up to 37 to 39 funds are random or independent, supporting the weak-form efficiency of the returns of the funds under study.